Kemampuan Pemecahan Masalah Matematis Siswa Kelas VII Dalam Menyelesaikan Persamaan Linear Satu Variabel - FKIP, Edumatica; Harahap, Elvira Riska; Surya, Edy (Edumatica : Jurnal Pendidikan Matematika, 2017)
Mathematical problem solving ability is a complex cognitive activity, as a process to fix a problem that is encountered and to complete the necessary number of strategies. Train students with problem solving in mathematics is not just expect students can solve problems or issues are given, but it is expected habits in the troubleshooting process allows him to live a life that is full complexity of the problem. Based on interviews with some seventh grade math teacher, obtained information that the students are still not familiar with the problems of solving problems and generally they are less able to write the resolution, especially concerning one variable linear equations. This study, a qualitative descriptive study.The subject of research as much as 3 wherein selecting the students backwardly random. Problem solving ability explored through interviews guided by the problem-solving abilities. Then analyzed descriptively qualitative. From the results of this study concluded that the S1 has a problem-solving ability is very high, while the S2 and S3 have an ample problem-solving abilities.